2015
DOI: 10.17503/agrivita-2015-37-3-p247-257
|View full text |Cite
|
Sign up to set email alerts
|

GENETIC DIVERSITY AMONG SUGARCANE (Saccharum officinarum L.) GENOTYPES AS SHOWN BY RANDOMLY AMPLIFIED POLYMORPHIC DNA (RAPD)

Abstract: This experiment was conducted to reveal genetic diversity among 38 genotypes of sugarcane (Saccharum officinarum L.) using RAPD markers. The population consisted of 8 genotypes from Australia, 7 from Africa, 10 from America, and 13 from Asia. Genetic similarity was ranging from 17% to 97% , with the average of 57%. UPGMA dendrograms divided the population into three major groups i.e. group 1, 2, and 3 which consisted of 23, 10, and 5 genotypes, respectively. Each major group comprised genotypes of different ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
(23 reference statements)
0
6
0
Order By: Relevance
“…Molecular markers that frequently used to assess genetic diversity are random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) markers. RAPD markers are more effective and efficient to determine the recombinant variability than morphological markers in assessing genetic diversity (Paul, Bandyophadyay, Acharyya, & Raychaudhuri, 2010;Hapsoro, Warganegara, Utomo, Sriyani, & Yusnita). RAPD markers also become a potential tool to identify genetic differences among varieties (Biswas, Akhond, Al-Amin, Khatun, & Kabir, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers that frequently used to assess genetic diversity are random amplified polymorphic DNA (RAPD), amplified fragment length polymorphism (AFLP) and simple sequence repeat (SSR) markers. RAPD markers are more effective and efficient to determine the recombinant variability than morphological markers in assessing genetic diversity (Paul, Bandyophadyay, Acharyya, & Raychaudhuri, 2010;Hapsoro, Warganegara, Utomo, Sriyani, & Yusnita). RAPD markers also become a potential tool to identify genetic differences among varieties (Biswas, Akhond, Al-Amin, Khatun, & Kabir, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Many study also reported that in many sugarcane crossing program around the world, the parents that used for crosses originated from inter-and intraspecific hybridization and its progenies. They results progenies with the same and share genetic makeup with parents (Stevenson, 1965;Zhang et al, 2001;Perera et al, 2012;Filho et al, 2010;Pan et al, 2003;Hapsoro et al, 2015;Chen et al, 2017). In contrast to previous result, in crosses between Erianthus sp.…”
Section: Discussionmentioning
confidence: 87%
“…4. Hapsoro, Warganegara, Utomo, Sriyani, & Yusnita (2015), also used RAPD markers on some sugarcane genotypes from Australia, Africa, America and Asia, found genetic similarities ranging from 17-97 % with an average genetic similarity of around 57 %. Fig.…”
Section: Fig 3 Electrophoresis Results Using Rapd Opn11 Primersmentioning
confidence: 99%